2004
DOI: 10.1073/pnas.0402699101
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic acid transport through carbon nanotube membranes

Abstract: We study the electrophoretic transport of single-stranded RNA molecules through 1.5-nm-wide pores of carbon nanotube membranes by molecular dynamics simulations. From Ϸ170 individual RNA translocation events analyzed at full atomic resolution of solvent, membrane, and RNA, we identify key factors in membrane transport of biopolymers. RNA entry into the nanotube pores is controlled by conformational dynamics, and exit by hydrophobic attachment of RNA bases to the pores. Without electric field, RNA remains hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
127
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(128 citation statements)
references
References 43 publications
0
127
0
1
Order By: Relevance
“…One example is the transport of microscopic particles, including atoms, ions, molecules, and colloids, through nanochannels, which is significant for fundamental biological processes and industrial applications as well. Examples include molecular or ionic permeation in zeolites [1,2], in carbon nanotubes [3,4], in aquaporins [5] and in ion channels [6][7][8]. In the present paper we report on molecular dynamics studies of the microscopic nonequilibrium transport of ions and water molecules through a nanochannel which shares structural similarities with a known biological potassium channel [9,10].…”
mentioning
confidence: 99%
“…One example is the transport of microscopic particles, including atoms, ions, molecules, and colloids, through nanochannels, which is significant for fundamental biological processes and industrial applications as well. Examples include molecular or ionic permeation in zeolites [1,2], in carbon nanotubes [3,4], in aquaporins [5] and in ion channels [6][7][8]. In the present paper we report on molecular dynamics studies of the microscopic nonequilibrium transport of ions and water molecules through a nanochannel which shares structural similarities with a known biological potassium channel [9,10].…”
mentioning
confidence: 99%
“…Very fast water transport through CNTs was predicted, because of the frictionless motion. Following the pioneering work on water molecule transport, the translocations of more complicated molecules, such as long chain polymer molecules 44 , DNA 45 and RNA 46 , through CNT were simulated as well. Simulations revealed that DNA molecules enter CNT spontaneously with the aid of van der Waals and hydrophobic interaction forces 47 and the translocation events can be driven by an electric field.…”
Section: Carbon Nanotube Based Nanopore/ Nanochannel Devicesmentioning
confidence: 99%
“…59 DNA has been passed through a 100 nm diameter carbon nanotube 60 and 50 nm wide hydrophilic channels. 61 It seems counter-intuitive that hydrophilic DNA would enter the hydrophobic interior of a SWCNT but theoretical simulations show that both RNA 62 and DNA 63 will translocate through 1.5 to 2 nm diameter tubes.…”
Section: Carbon Nanotube Based Nanopore/ Nanochannel Devicesmentioning
confidence: 99%
“…They found that the ssDNA either inserted into the nanotube or wrapped around the outside, depending on the SWNT diameter. Several other groups performed further simulations on the encapsulation of DNA, RNA, and other biomolecules into SWNTs [21,22,23,24]. We are not aware of any detailed studies of the adsorption of nucleic acids on the outside of SWNTs.…”
Section: Molecular Dynamics Simulations Of Nucleotide Adsorption Ontomentioning
confidence: 99%